Matching Low Viscosity with Enhanced Conductivity in Vat Photopolymerization 3D Printing: Disparity in the Electric and Rheological Percolation Thresholds of Carbon-Based Nanofillers Is Controlled by the Matrix Type and Filler Dispersion - Sevriugina, Veronika; Pavliňák, David; Ondreáš, František; Jašek, Ondřej; Štaffová, Martina; Lepcio, Petr (AMER CHEMICAL SOC, 2023)
This study investigated the impact of carbonaceous fillers (carbon black, multiwalled carbon nanotubes, graphene, and highly defective graphene) on aromatic and nonaromatic photopolymer resins' properties, such as viscosity, long-term stability, complex permittivity, curing efficiency, final conversion, storage modulus, heat deflection and glass transition temperatures, network density, and DC resistivity. The presented results also highlight challenges that must be addressed in designing and processing carbonaceous filler-based 3D-printed photopolymer resins. The improved dielectric and electrical properties were closely tied to the dispersion quality and filler-matrix affinity. It favored the enhanced dispersion of anisotropic fillers (nanotubes) in a compatible matrix above their percolation threshold. On the other hand, the dispersed filler worsens printability due to the elevated viscosity and deteriorated penetration depth. Nonetheless, electrical and rheological percolation was found at different filler concentrations. This window of despaired percolation combines highly enhanced conductivity with only mildly increased viscosity and good printability.

This study investigated the impact of carbonaceous fillers (carbon black, multiwalled carbon nanotubes, graphene, and highly defective graphene) on aromatic and nonaromatic photopolymer resins' properties, such as viscosity, long-term stability, complex permittivity, curing efficiency, final conversion, storage modulus, heat deflection and glass transition temperatures, network density, and DC resistivity. The presented results also highlight challenges that must be addressed in designing and processing carbonaceous filler-based 3D-printed photopolymer resins. The improved dielectric and electrical properties were closely tied to the dispersion quality and filler-matrix affinity. It favored the enhanced dispersion of anisotropic fillers (nanotubes) in a compatible matrix above their percolation threshold. On the other hand, the dispersed filler worsens printability due to the elevated viscosity and deteriorated penetration depth. Nonetheless, electrical and rheological percolation was found at different filler concentrations. This window of despaired percolation combines highly enhanced conductivity with only mildly increased viscosity and good printability.
Matching Low Viscosity with Enhanced Conductivity in Vat Photopolymerization 3D Printing: Disparity in the Electric and Rheological Percolation Thresholds of Carbon-Based Nanofillers Is Controlled by the Matrix Type and Filler Dispersion
Keywords: MOLECULAR MOBILITY; NANOCOMPOSITES; SPECTROSCOPY; PARAMETERS; NANOTUBES; MOLECULAR MOBILITY; NANOCOMPOSITES; SPECTROSCOPY; PARAMETERS; NANOTUBES